2010
DOI: 10.1186/1471-213x-10-34
|View full text |Cite
|
Sign up to set email alerts
|

The function and regulation of the bHLH gene, cato, in Drosophila neurogenesis

Abstract: BackgroundbHLH transcription factors play many roles in neural development. cousin of atonal (cato) encodes one such factor that is expressed widely in the developing sensory nervous system of Drosophila. However, nothing definitive was known of its function owing to the lack of specific mutations.ResultsWe characterised the expression pattern of cato in detail using newly raised antibodies and GFP reporter gene constructs. Expression is predominantly in sensory lineages that depend on the atonal and amos pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Enhancer analysis revealed that cato too has separable Ch and ES enhancers [27]. The former contains an E ATO site that is required for Ch expression, and it is ectopically activated upon misexpression of ato .…”
Section: Resultsmentioning
confidence: 99%
“…Enhancer analysis revealed that cato too has separable Ch and ES enhancers [27]. The former contains an E ATO site that is required for Ch expression, and it is ectopically activated upon misexpression of ato .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Hes5 Drosophila homolog, E(Spl), was found to be a target of both atonal and Scute (Reeves and Posakony, 2005; Aerts et al, 2010). Although multiple genes have been identified downstream of Atoh1 (such as Nr2f6 and Cbln2) or atonal (mouse homologs Cdkn1a and Tacr3) (Powell et al, 2004; Krizhanovsky et al, 2006; Sukhanova et al, 2007; Miesegaes et al, 2009; zur Lage and Jarman, 2010) additional experiments are required to determine if these are direct and constitute neuronal subtype specific targets. Recently, genome-wide scale identification of atonal targets has suggested that atonal does not directly activate terminal differentiation genes, but instead activates molecules in major signaling pathways (Aerts et al, 2010); however, another analysis found that atonal was able to directly activate at least one differentiation gene (Cachero et al, 2011) and it is known that the related bHLH factor, chick Atoh7, can directly activate a terminal differentiation gene in the retina (Skowronska-Krawczyk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An alignment of the Atoh1 common E-box to consensus binding sites identified for atonal , Ascl1 , Neurog/Neurod1 , and MyoD (Bertrand et al, 2002; Powell et al, 2004; Castro et al, 2006; Seo et al, 2007; Cao et al, 2010) reveals only subtle differences (Figure 5I). The differences between the Atoh1 and ato E-boxes (Figure 5I, arrowhead) (Ben-Arie et al, 1996; Chien et al, 1996; Ben-Arie et al, 2000; Wang et al, 2002) may be due to the differences in function with which the targets were identified (neuronal subtype specification versus differentiation) or the few targets used to form both E-box sequences (Powell et al, 2004; zur Lage and Jarman, 2010). Slight differences in the bHLH consensus sequences may represent true binding preferences in vivo; however, it seems more likely that bHLH factors work with other factors to carry out neuronal subtype specific programs.…”
Section: Discussionmentioning
confidence: 99%
“…amos is a proneural gene that regulates the development of two classes of olfactory neurons and a class of multidendritic neurons [15,17,18]. cato , which is widely expressed in PNS after the selection of neural precursors and before their terminal differentiation, is required for proper sensory neuron morphology [16,19]. …”
Section: The Evolution Of Atonal Homologsmentioning
confidence: 99%